Using Different Low-Profile Abutments for Assisting Mandibular Implant Overdenture: A Split-Mouth Study - Ahmed K. Khalifa; Mohammad Mahmoud Alokda; Mohamed Moustafa Said (Hindawi Limited, 2022)
Background. Using a pair of different low-profile abutments to assist mandibular implant overdenture (MIOD) in limited restorative space is questionable due to the different morphology. Objective. To investigate the marginal bone level (MBL) change and peri-implant-tissue health (PITH) around a pair of OT Equator® and Locator® suprastructures assisting MIOD. Methods. Seventeen edentulous patients received MIOD assisted by OT Equator® and Locator®. MBL change was investigated at the implant loading (T1), after six months (T2) and twelve months (T3) of implant loading. PITH was evaluated at T2 and T3. Results. There was within abutment significant difference in MBL change after T2 and T3 of loading for Locator (0.05 ± 0.02 and 0.32 ± 0.08, respectively) P=0.01; and for Equator (0.11 ± 0.08 and 0.21 ± 0.09, respectively) P=0.01. Also, there was a significant difference between Locator and Equator on the modified plaque index (MPI) after T3 P=0.01. The significant results were recorded for the MPI at T2 and T3 for Locator (0.92 ± 0.26 and 1.5 ± 0.51, respectively) P=0.01 and for Equator (0.82 ± 0.26 and 1.42 ± 0.51, respectively) P=0.003. For modified bleeding index, there was significant difference at T2 and T3 for Locator (0.57 ± 0.19 and 1.14 ± 0.41, respectively) P=0.03 and for Equator (0.46 ± 0.22 and 1.07 ± 0.41, respectively) P=0.01. For gingival index, there was significant difference at T2 and T3 for Locator (0.57 ± 0.11 and 1.28 ± 0.35, respectively) P=0.001 and for Equator (0.35 ± 0.21 and 1.1 ± 0.46, respectively) P=0.001. Conclusions. Using different pairs of the low-profile OT Equator® and Locator® abutments to assist MIOD is clinically acceptable based on the MBL change and PITH outcomes.